Green synthesis and characterisation of ZnO from citrus hystrix extracts for photocatalytic application - Lauthfi, Muhammad Asyraf Al-Wafiy; Mohd Yusoff, Mohd Zaki; Ahmad Kamil, Suraya; Che Azurahanim, Che Abdullah; Malek, Mohd Firdaus (2024)
The purpose of this ongoing research project is to enhance the quality of zinc oxide (ZnO) powder synthesised through a green synthesis process using extracts from C. hystrix. The objective is to explore the potential of C. hystrix as a sustainable source for the production of ZnO nanoparticles with improved properties. Through a series of experimental procedures, including characterisation techniques such as x-ray diffraction (XRD), scanning electron microscopy (SEM), and UV–vis spectroscopy, the synthesised ZnO powder's structural, morphological, and optical properties are evaluated. Additionally, the photocatalytic activity of the biosynthesised ZnO powder is assessed for its effectiveness in degrading organic pollutants under UV illumination. By systematically optimising the synthesis parameters and understanding the underlying mechanisms, this research endeavours to contribute to the advancement of green synthesis approaches for producing high-quality ZnO nanoparticles that demonstrate enhanced performance, thereby fostering sustainable and eco-friendly nanomaterial synthesis processes. Following the successful production of eco-friendly ZnO through green synthesis, the optimum sample will undergo several experiments using a doping method with various chemical substances.